Perilaku Pencarian Informasi Remaja Akhir Mengenai Hobi: Studi Kasus Pemanfaatan Aplikasi TikTok - Oktaviani, Eka; Rachman, Yeni Budi (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2022)
The current rapid technological development and the various social restrictions caused by the COVID-19 pandemic are encouraging people to seek out information about their interests on the World Wide Web, specifically on social media. Taking into account the virality of TikTok as a social media platform amongst young people, this research aims to explore the information seeking behavior of young adults on said application, as well as what sort of hindrance they might come across whilst using TikTok. This descriptive qualitative research is a case study that is done by semi-structured interviews and observations. The data gathered through those methods are then analyzed using Niedźwiedzka’s Information Behavior Model (2003). The results of this research show that the information seeking behavior of young adults on TikTok are in accordance with Niedźwiedzka’s Information Behavior Model. Although, there still appear to be some seemingly interchangeable steps within those activities. This research recommends that both individual users as well as institutional ones, like libraries, to be wiser with the usage of apps such as TikTok and the potential it has to be used as an outreach and promotional tool.